The Too-Much-Precision Effect: When and Why Precise Anchors Backfire With Experts. (December 2016) - Loschelder, David D.; Friese, Malte; Schaerer, Michael; Galinsky, Adam D.
Past research has suggested a fundamental principle of price precision: The more precise an opening price, the more it anchors counteroffers. The present research challenges this principle by demonstrating a too-much-precision effect. Five experiments (involving 1, 320 experts and amateurs in real-estate, jewelry, car, and human-resources negotiations) showed that increasing the precision of an opening offer had positive linear effects for amateurs but inverted-U-shaped effects for experts. Anchor precision backfired because experts saw too much precision as reflecting a lack of competence. This negative effect held unless first movers gave rationales that boosted experts' perception of their competence. Statistical mediation and experimental moderation established the critical role of competence attributions. This research disentangles competing theoretical accounts (attribution of competence vs. scale granularity) and qualifies two putative truisms: that anchors affect experts and amateurs equally, and that more precise prices are linearly more potent anchors. The results refine current theoretical understanding of anchoring and have significant implications for everyday life.